Rare and Complicated Granulomatous Lobular Mastitis (2000–2023): A Bibliometrics Study and Visualization Analysis - Zhang M; Pu D; Feng D; Shi G; Li J (Dove Medical Press, 2024)
Mengdi Zhang,1 Dongqing Pu,1 Dandan Feng,1 Guangxi Shi,2 Jingwei Li2 1First Clinical Medical College, Shandong University of Traditional Chinese Medicine, Jinan City, People's Republic of China; 2Department of Thyroid and Breast Diagnosis and Treatment Center, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan City, People's Republic of ChinaCorrespondence: Jingwei Li, Department of Thyroid and Breast Surgery, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan City, People's Republic of China, Email 71000395@sdutcm.edu.cnPurpose: Granulomatous mastitis (GLM) is a rare and complex chronic inflammatory disease of the breast with an unknown cause and a tendency to recur. As medical science advances, the cause, treatment strategies, and comprehensive management of GLM have increasingly attracted widespread attention. The aim of this study is to assess the development trends and research focal points in the GLM field over the past 24 years using bibliometric analysis.Methods: Using GLM, Granulomatous mastitis (GM), Idiopathic granulomatous lobular mastitis (IGLM), and Idiopathic granulomatous mastitis (IGM) as keywords, we retrieved publications related to GLM from 2000 to 2023 from the Web of Science, excluding articles irrelevant to this study. Citespace and VOSviewer were employed for data analysis and visualization.Results: A total of 347 publications were included in this analysis. Over the past 24 years, the number of publications has steadily increased, with Turkey being the leading contributor in terms of publications and citations. The University of Health Sciences, Istanbul University, and Istanbul University Cerrahpasa were the most influential institutions. The Breast Journal, Breast Care, and Journal of Investigative Surgery were the journals that published the most on this topic. The research primarily focused on the cause, differential diagnosis, treatment, and comprehensive management of GLM. Issues related to recurrence, hyperprolactinemia, and Corynebacterium emerged as current research hotspots.Conclusion: Our bibliometric study outlines the historical development of the GLM field and identifies recent research focuses and trends, which may aid researchers in identifying research hotspots and directions, thereby advancing the study of GLM.Keywords: granulomatous lobular mastitis, bibliometric analysis, visual analysis, knowledge graphs, review